Orthogonal Frequency Division Multiplexing for Wireless Communications - Li, Ye Geoffrey; Stuber, Gordon L. (Signals and Communication Technology, 2006)
OFDM (Orthogonal frequency division multiplexing} has been shown to be an effective technique to combat multipath fading in wireless channels. It is being used in various wireless communication systems such as in Digital Audio Broadcasting (DAB) and Video Broadcasting (DVB) in Europe and many of IEEE 802.11 and IEEE 802.16 standards. This book provides a comprehensive introduction to the theory and practice of OFDM for wireless communications. It includes basic concepts of OFDM, performance optimization, time- and frequency-offset estimation, channel estimation, peak-to-average power ratio reduction, and MIMO OFDM techniques. The key concepts are developed with detailed derivations and proofs to make the material accessible and easy to follow by both students and professionals. While chapters have been written by experts in their respective subject area, the authors have tried to make symbols, notations, presentations and styles consistent. To facilitate readers, the material includes extensive references as well as a large and useful index at the end of the book. OFDM for Wireless Communications is highly recommended for graduate level courses in advanced digital communication and professional seminars and tutorials on wireless OFDM.